Comparative analyses of Defense gene expression in Norway spruce sapwood - Rommel, Sophie (2012)
As the most important species in Europe’s forest industry, Norway spruce [Picea abies (L.) Karst.] has a very high economical impact. Unfortunately, the forest industry has yearly losses of approximately 800 million euro, because many Norway spruce stands suffer infection by one of the tree’s major pathogens Heterobasidion parviporum (Fr.) Niemelä & Korhonen.